Academic mobility in Latin America and the Caribbean: patterns and prospects - Christine, Farrugia, (Revista Educación Superior y Sociedad (ESS), 2019)
While its scale has been relatively limited, international student and scholar mobility to and from Latin America and the Caribbean has played a growing role in the internationalization of higher education institutions in recent years. This article describes the current landscape of international higher education mobility in Latin America and the Caribbean, including the region’s global position in international mobility; the current scale and patterns of inbound and outbound students and scholars; analysis of the drivers of mobility; and discussion of future prospects. .